Linking the heart and brain in type 2 diabetes: association between global longitudinal strain and cognitive function - Barutta, Federica; Andreis, Alessandro; Bollati, Martina; Ferro, Arianna; Bellini, Stefania; Gioiello, Giulia; Mengozzi, Giulio; Bellettini, Matteo; De Ferrari, Gaetano M.; Alunni, Gianluca; Broglio, Fabio; Beccuti, Guglielmo; et al. (Frontiers in Endocrinology, 2025)
IntroductionCognitive impairment is a frequent complication of type 2 diabetes (T2DM). Global longitudinal strain (GLS), an echocardiographic marker of subclinical left ventricular (LV) systolic dysfunction, has been associated with adverse cardiovascular outcomes in T2DM. However, its relationship with cognitive performance remains unexplored. The aim was to investigate the association between GLS and cognitive function in patients with T2DM.MethodsWe prospectively enrolled 234 T2DM patients without hemodynamically significant carotid stenosis, history of stroke or severe hypoglycemia. Cognitive function was assessed using the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) and GLS measured via speckle-tracking echocardiography. Multivariable linear regression models were used to evaluate associations between GLS and RBANS scores. Sensitivity analyses excluded individuals with coronary heart disease (CHD), atrial fibrillation (AF), or LV ejection fraction (LVEF) <50%.ResultsThe mean RBANS total score was 96.7 ± 17.1; 19.7% of participants scored <80, indicating borderline/impaired cognition. Mean GLS was −19.23 ± 2.59%, with 29.1% of patients showing subclinical LV dysfunction (GLS ≥ −18%). Unlike LVEF, impaired GLS (≥ −18%) was associated with lower RBANS total scores. This association remained significant after excluding individuals with CHD, AF, or LVEF<50%, and after adjusting for age, sex, education, lifestyle factors, metabolic and hemodynamic parameters. Educational attainment modified the association, with stronger GLS-cognition links in participants with lower education. The relationship was unaffected by adjustment for markers of inflammation and endothelial dysfunction.ConclusionsIn patients with T2DM, impaired GLS is independently associated with reduced cognitive performance, even in patients with normal LVEF.